Effect of Dynamic Geometry Software on 3-Dimensional Geometric Shape Drawing Skills - Kepceoğlu, İbrahim (Redfame Publishing, 2018)
In order to be able to draw accurately and to interpret the drawings properly, the skills of the students' drawing skills and therefore spatial visualization and spatial orientation must be developed. The studies in the literature are mostly concerned with examining the spatial skills of students with various models or investigating the effects of different methods and techniques on the spatial skills of students. For this reason, the effect of dynamic geometry software on the three-dimensional shapes of elementary school mathematics teacher candidates has been examined in this study. The mixed method research paradigm is chosen as the methodology of this study. This research involves two parts: the first is, under quantitative paradigm, the true experiment and the second is, under qualitative paradigm, case study. In the true experimental design. 30 pre-service elementary mathematic teachers are divided randomly into two groups as control and experiment group. 15 pre-service teachers in the experiment group participated to the Cabri 3D Plus workshop for 3 weeks. According to the results of the research, it is revealed that the candidates of the Cabri 3D program have an effect on the drawing of three dimensional geometric shapes.
Keywords: 4. Education